2019
DOI: 10.1016/s0140-6736(18)31665-9
|View full text |Cite
|
Sign up to set email alerts
|

How long does a hip replacement last? A systematic review and meta-analysis of case series and national registry reports with more than 15 years of follow-up

Abstract: Summary Background Total hip replacement is a common and highly effective operation. All hip replacements would eventually fail if in situ long enough and it is important that patients understand when this might happen. We aimed to answer the question: how long does a hip replacement last? Methods We did a systematic review and meta-analysis with a search of MEDLINE and Embase from the start of records to Sept 12, 2017. We included articles reporting 15-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
272
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 444 publications
(290 citation statements)
references
References 24 publications
3
272
1
14
Order By: Relevance
“…Our studies, in which we report the results for hips and knees in two parallel articles, provide the first generalizable survival estimates for hip and knee replacements at 25 years [7,8]. In each, we conducted a systematic review and meta-analysis of case-series using a single construct reporting survival estimates with mean follow-up of more than 15 years.…”
Section: Expert Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies, in which we report the results for hips and knees in two parallel articles, provide the first generalizable survival estimates for hip and knee replacements at 25 years [7,8]. In each, we conducted a systematic review and meta-analysis of case-series using a single construct reporting survival estimates with mean follow-up of more than 15 years.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Compared to overall pooled results demonstrating 86% survival at 15 years, we observed survival of 95% in these four constructs (Exeter V40/Trident, Exeter V40/Exeter Contemporary, CPT/Trilogy, and CPT/ZCA). However, these constructs only account for 25% of THRs implanted in England and Wales in 2016 [7]. A recent network meta-analysis concluded that newer THR implant combinations were not superior to a reference implant combination (metal-on-polyethylene, small head, cemented), which may now be considered 'old technology' [12].…”
Section: Implant Design and Component Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total hip arthroplasty (THA) is so successful in restoring mobility and relieving pain in patients with degenerated hip joints [1] that it has been nominated as the operation of the 20th century [2]. Failure, however, remains an issue, with between one-third and nearly half of THA procedures requiring postoperative revision within 30 years [3,4]. One of the possible causes of failure is trunnionosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is one of the most successful and cost‐effective solutions to address osteoarthritis of the hip. THA has been called “the operation of the century" 1 due to its revolutionary impact on the management of elderly patients crippled with arthritis, and relatively long survivorship of 25 years for about 58% of treated patients 2 . Nevertheless, hip replacements have also multiple failure modes including instability, infection, periprosthetic fracture, and a combination of expected tribological and biological loosening and wear 3,4 .…”
Section: Introductionmentioning
confidence: 99%